Algorithmic Aspects in Information and Management 6th International Conference, AAIM 2010, Weihai, China, July 19-21, 2010. Proceedings - Chen, Bo. (Lecture Notes in Computer Science, 2010)
This volume constitutes the proceedings of the International Conference on Algorithmic Aspects in Information and Management, AAIM 2010, held in Weihai, China, in July 2010.